Steam flow pressure reduction valve mass flow calculation - Poljak, Igor, inženjer brodostrojarstva (Array, 2019)
In this paper an analysis of the three different calculation methods for the steam mass flow through the linear pressure reduction valve is presented. Two different makers developed their own mass flow calculation method while one is following recommendation as per ISO standard calculation guidance. All three methods were varied and compared. For calculation model a superheated steam reduction valve was taken, which is reducing superheated steam pressure from 6 to 2 MPa, with fixed Kv value and with variations of the inlet superheated steam temperature from 310 to 280 °C.